Fully automated one-pot two-step synthesis of 4-[18F]-ADAM, a potent serotonin transporter imaging agent. (April 2016) - Cheng, Cheng-Yi; Chou, Ta-Kai; Shiue, Chyng-Yann
Abstract: Introduction: N, N -dimethyl-2-(2-amino-4-[ 18 F]fluorophenylthio)benzylamine (4-[ 18 F]-ADAM, 2 ) is a potent serotonin transporter (SERT) imaging agent. In order to fulfill the demand of clinical studies, we have developed a fully automated one-pot two-step synthesis of this potent SERT imaging agent. Methods: The 4-[ 18 F]-ADAM (2 ) was synthesized using a commercially available GE TRACERlab FN module. Briefly, the precursor, N, N -dimethyl-2-(2, 4-dinitrophenylthio) benzylamine (1 ) in DMSO was reacted with K[ 18 F]/K2.2.2 in a glassy carbon reaction vessel at 120 °C for 7.5 min followed by reduction of the intermediate with NaBH4 /Cu(OAc)2 in EtOH in the same vessel at 80 °C for 20 min. The reaction mixture was then purified with high-performance liquid chromatography (HPLC) and solid phase extraction (SPE) to give (2 ). The quality of (2 ) synthesized by this method was verified by HPLC and TLC as compared to its authentic sample synthesized by two-pot two-step method. Results: Using this automated one-pot two-step method, the radiochemical yield (RCY) of (2 ) was 2.5±0.8% ( n =12, EOS) in a synthesis time of 100±6 min from EOB with a specific activity of 4.4±1.9 Ci/μmol ( n =12, EOS). Radioligand (2 ) was stable over 4 h at room temperature. Conclusions: This fully automated one-pot two-step synthetic method using a commercially available GE TRACERlab FN module could simplify the synthesis of 4-[ 18 F]-ADAM (2 ) and fulfill its demand for both animal and human studies, especially for study sites without a cyclotron. Highlights: 4-[ 18 F]-ADAM (2 ) was prepared by one-pot two step method with TRACERlab FN module. The RCY (2 ) was 3%, synthesis time was 100 min and SA was 5.0 Ci/μmol (EOS). The concentration of EtOH, ACN and DMSO in (2 ) were 10, 0.04, 0.5%, respectively. (2 ) prepared by this method is suitable for both animals and human studies.